Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/0148607114531046
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aluminum Concentrations in Pediatric Patients Receiving Long‐Term Parenteral Nutrition

Abstract: Pediatric patients receiving long-term PN for IF in Canada are at risk for Al toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
19
0
2
Order By: Relevance
“…When peripheral PN is infused, solution' osmolarity of less than 900 mosmol/l reduces the risk of thromboflebitis [102e104] (LOE 3). Pediatric patients receiving long-term PN are at risk for aluminium toxicity and consequential MBD even at present [113,114] (LOE 2þþ). Neonates who are exposed to parenteral aluminum intake may have reduced lumbar spine and hip bone mass during adolescence, which may predispose to osteoporosis and hip fracture later in life [115] (LOE 1À).…”
Section: Osmolaritymentioning
confidence: 99%
“…When peripheral PN is infused, solution' osmolarity of less than 900 mosmol/l reduces the risk of thromboflebitis [102e104] (LOE 3). Pediatric patients receiving long-term PN are at risk for aluminium toxicity and consequential MBD even at present [113,114] (LOE 2þþ). Neonates who are exposed to parenteral aluminum intake may have reduced lumbar spine and hip bone mass during adolescence, which may predispose to osteoporosis and hip fracture later in life [115] (LOE 1À).…”
Section: Osmolaritymentioning
confidence: 99%
“…19 When plasma aluminum concentrations were measured in patients with intestinal failure who were receiving long-term parenteral nutrition, the average concentration was 8 times greater than that in healthy controls. 20 The aluminum concentrations present in smallvolume parenteral nutrition solutions have not changed since the studies that revealed a developmental effect were published. Unfortunately, until new parenteral components with lower aluminum content are available, no matter how thoughtful the prescriber, parenteral nutrition solutions for most pediatric patients will contain aluminum concentrations above the recommended amount.…”
Section: Regulatory Responsementioning
confidence: 99%
“…The contamination of aluminum in PN solutions has been a concern as aluminum toxicity can cause bone disease, neurological impairment, liver disease, and anemia even years after initial exposure . Although aluminum content in PN has significantly decreased in the last years, high aluminum levels are still reported in children receiving PN . Calcium and phosphate salts and multivitamin and trace element solutions are now the primary sources for aluminum contamination in PN .…”
Section: Monitoring Of Long‐term Complicationsmentioning
confidence: 99%
“…Calcium and phosphate salts and multivitamin and trace element solutions are now the primary sources for aluminum contamination in PN . The US Food and Drug Administration has advised that PN solutions are required to contain <25 mcg/L of aluminum with a daily intake of <5 mcg/kg/day . PN solutions should be labeled with the maximum aluminum content in home PN patients and in inpatients receiving PN, especially neonates due to immature kidney function.…”
Section: Monitoring Of Long‐term Complicationsmentioning
confidence: 99%